The case for indicator condition‐guided HIV screening. Issue 7 (10th March 2013) - Lazarus, JV; Hoekstra, M; Raben, D; Delpech, V; Coenen, T; Lundgren, JD; ,
<x xml:space="preserve">Abstract</x> One‐half of the estimated 2.5 million people who now live with HIV in the World Health Organization (WHO) European Region are still diagnosed late. A central question is which clinical scenarios should trigger an HIV test recommendation in order to avoid late presentation. Drawing on the work of the HIV Indicator Diseases across Europe Study (HIDES), new guidance brings together in one place a list of the conditions that should result in an HIV screening recommendation.